Afrikology and Transdisciplinarity : a Restorative Epistemology. - Nabudere, Dani Wadada (Africa Institute of South Africa, 2012)
This monograph is intended to examine the epistemology of restorative rights in view of the continuing violation of rights in all aspects of life on the African continent and other parts of the world. It is based on the research, which the Marcus Garvey Pan-Afrikan Institute undertook between 2006ñ2008, under a cross-disciplinary research project entitled Restorative Justice and its Relationship to International Humanitarian Law, which resulted in a Comprehensive Report that was later discussed at an international conference in Nairobi in August 2008. This conference was opened by the Prime Mi.